Quality standardization - a factor of sustainable competitiveness of enterprises in Serbia - Miletic, Vuk; Ćurčić, Nikola; Simonović, Zoran (Anali Ekonomskog fakulteta u Subotici, 2020)
The analysis of the possibilities of creating the sustainable competitiveness of an enterprise from the point of view of the functional uniformity of economic and ecological sustainability, as well as the production of products in compliance with the international standards for business operations, is the subject matter of the research conducted in this paper. The achievement of a higher level of competitiveness is a strategic goal of every enterprise, while the competitiveness of a product implies an appropriate standardization of quality. The starting assumption is that in order for enterprises to become competitive not only on the domestic market, but on the international market as well, it is necessary that they should standardize their business operations by improving the quality system. The goal is to gain an insight into how much significance domestic enterprises give to the standardization of quality, apart from the other needed factors, how interested they are in investing in the implementation of the ISO 9000:2000 standards, which are primarily oriented towards the satisfaction of client requirements, thus improving their own business operations. In this research study, the hypothetical–deductive methods, analytical-deductive and comparative methods, historical and statistical–descriptive methods, as well as the comparative statistical methods (ch2 Test, ANOVA), are used.